Confirmation of the Luminous Blue Variable Status of MWC 930 - A. S. Miroshnichenko; N. Manset; S. V. Zharikov; J. Zsargó; J. A. Juárez Jiménez; J. H. Groh; H. Levato; M. Grosso; R. J. Rudy; E. A. Laag; K. B. Crawford; R. C. Puetter; et al. (Advances in Astronomy)
We present spectroscopic and photometric observations of the emission-line star MWC 930 (V446 Sct) during its long-term optical brightening in 2006–2013. Based on our earlier data we suggested that the object has features found in Luminous Blue Variables (LBV), such as a high luminosity (~3 105 L⊙), a low wind terminal velocity (~140 km s−1), and a tendency to show strong brightness variations (~1 mag over 20 years). For the last ~7 years it has been exhibiting a continuous optical and near-IR brightening along with a change of the emission-line spectrum appearance and cooling of the star’s photosphere. We present the object’s V-band light curve, analyze the spectral variations, and compare the observed properties with those of other recognized Galactic LBVs, such as AG Car and HR Car. Overall we conclude the MWC 930 is a bona fide Galactic LBV that is currently in the middle of an S Dor cycle.